Protective Role of Quercetin plus Vitamin C on Infection of Rats with Klebsiella pneumoniae and Pseudomonas aeruginosa (Medico Legal Update, 2020)
This study was performed on fifty adult male laboratory rats (Rattus norvegicus) of 175 – 200 grams weights. The animals were randomly allocated into five equal groups of ten rats each. The groups of rats were: First, control group where the animals were fed on a standard diet along the experiment period; the Second and Fourth groups, where also maintained on a standard diet while the Third and Fifth groups were also maintained on a standard diet and they were orally dosed with Quercetin (20 mg) and vitamin C (500 mg) daily. Suspension in phosphate buffer solution (PBS) was made for the bacteria and colony forming unit (CFU) count was done after making 10-folds serial dilutions. The rats of the second and third groups were intramuscularly injected with 16×106 (CFU) of Klebsiella pneumoniae while those of fourth and fifth groups were intramuscularly injected with 20×105 (CFU) of Pseudomonas aeruginosa. After 48 hours of challenge with bacteria, all the rats of the second group and 4 rats of the third group died. On the other hand, all the rats of fourth group and 3 rats of the fifth group died. The organs of died animals of all groups like the stomach, spleen, liver, and thigh muscle were immediately picked up and weighed after death and well homogenized with (PBS) to obtain counting of (CFU) in the organs mentioned. Passing 3 days later, the survived 6 rats of third group and the survived 5 rats of fifth group were euthanized and their organs were treated as the same as the process mentioned before to gain the organs (CFU) count. The results in this study clarify that the use of Quercetin plus vitamin C has led to increase the survival of rats challenged with bacterial infection and the organs bacterial count of them was significantly less than those rats maintained without supplementation with Quercetin and vitamin C at (P?0.05).